2011
DOI: 10.1042/bsr20100064
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the contribution of the elemental composition of fetal calf serum to antigenic expression of primary human umbilical-vein endothelial cells in vitro

Abstract: One of the major obstacles to obtaining human cells of a defined and reproducible standard suitable for use as medical therapies is the necessity for FCS (fetal calf serum) media augmentation in routine cell culture applications. FCS has become the supplement of choice for cell culture research, as it contains an array of proteins, growth factors and essential ions necessary for cellular viability and proliferation in vitro. It is, however, a potential route for the introduction of zoonotic pathogens and makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…Most in vitro culturing of cell monolayers requires the presence of serum in the culture medium to allow for the cells to adhere and grow, in which the most commonly used is FCS (Bryan et al 2011). The FCS has obvious inherent effects on the cultured cells, which varies between cell types and their differentiation status (Lund et al 2009;Bryan et al 2011).…”
Section: Cell Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most in vitro culturing of cell monolayers requires the presence of serum in the culture medium to allow for the cells to adhere and grow, in which the most commonly used is FCS (Bryan et al 2011). The FCS has obvious inherent effects on the cultured cells, which varies between cell types and their differentiation status (Lund et al 2009;Bryan et al 2011).…”
Section: Cell Stimulationmentioning
confidence: 99%
“…The FCS has obvious inherent effects on the cultured cells, which varies between cell types and their differentiation status (Lund et al 2009;Bryan et al 2011). Since FCS contains vast amounts of EVs, most studies perform an EV depletion protocol of FCS before using it for production of CM, or change to serum-free medium (Shelke et al 2014).…”
Section: Cell Stimulationmentioning
confidence: 99%
“…It has been previously shown that differences in serum composition lead to statistical differences in experimental outcomes [40]. The disadvantages of FBS, such as undefined composition or batch-to-batch variations, have been known for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in spontaneous mineralization between the four FBS types used can be explained by differences in elemental composition. It is known that sera exhibit significant differences in composition between different types and batches [2,40]. The elemental composition of FBS, or sera in general, is not defined.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of these media includes certain vitamins and minerals, but unfortunately, in many common culture media, the only source of micronutrients is fetal bovine serum (FBS), which contributes to only 5–10% of the media composition. Moreover, the appropriate proportion of micronutrients is not always provided because the precise composition of each batch of FBS is in fact extremely variable [34]. …”
Section: Introductionmentioning
confidence: 99%